DOUBLE RIGHT ATRIUM OR CORTRIATRIUM DEXTRUM A RARE ENTITY:A CASE REPORT - Muhammad Furrakh Maqbool; Khalil Iqbal et al. (Journal of University Medical & Dental College, 2016)
ABSTRACT:Cortriatrium dextrum is an extremely rare congenital anomaly .Mostly the anomaly is diagnosed on autopsy as an isolated ﬁnding or associated with some other congenital disorder. We report a case of young female presented with palpitation and a systolic murmur.